18F-FDG PET/CT and PET for evaluation of pathological response to neoadjuvant chemotherapy in breast cancer: a meta-analysis - Cheng, Xu; Li, Yongjun; Liu, Biao; Xu, Zhaoqiang; Bao, Lihua; Wang, Jie (Acta radiologica (1987), 2012)
Neoadjuvant chemotherapy is increasingly the treatment for patients with inoperable breast cancer. Considering the side-effects of chemotherapy, there is a need for early evaluating response to neoadjuvant chemotherapy. To determinate the diagnostic performance of 18F-fluorodeoxyglucose position emission tomography/computed tomography (FDG PET/CT) and FDG PET for evaluating response to neoadjuvant chemotherapy in patients with breast cancer. "PubMed" (MEDLINE included) database, EMBASE, and Cochrane Database of Systematic Reviews were searched for relevant articles. We assessed the methodological quality of included study with Quality Assessment of Diagnosis Accuracy Studies (QUADAS) score tool, and used "Meta-DiSc" statistic software to obtain pooled estimates of sensitivity, specificity, diagnostic odds ratio (DOR), and summary receiver-operating characteristic (SROC) curve. Seventeen studies (a total of 781 subjects) met the inclusion criteria. The pooled sensitivity was 0.840 (95% confidence interval [CI] 0.796-0.878). The pooled specificity was 0.713 (95% CI 0.667-0.756). For FDG PET/CT (10 studies included), the pooled sensitivity was 0.847 (95% CI 0.793-0.892), the pooled specificity was 0.661 (95% CI 0.598-0.720). The pooled likelihood ratio (LR+), negative likelihood ratio (LR-), and diagnostic odds ratio (DOR) were 2.835 (95% CI 1.640-4.900), 0.221 (95% CI 0.160-0.305), and 17.628 (95% CI 7.431-41.818). The area under the SROC curve (AUC) was 0.8934. For FDG PET (7 studies included), the pooled sensitivity and specificity were 0.826 (95% CI 0.741-0.892) and 0.789 (95% CI 0.719-0.849). The pooled LR + , LR-, and DOR were 3.601 (95% CI 2.601-4.986), 0.242 (95% CI 0.157-0.374), and 13.641 (95% CI 7.433-25.030). The AUC was 0.8764. Our results indicate that FDG PET/CT and PET have reasonable sensitivity in evaluating response to neoadjuvant chemotherapy in breast cancer; however, the specificity is relative low. The combination of other imaging methods with FDG PET/CT or PET is recommended.